2018
DOI: 10.2174/0929867325666180309110629
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 10 Inhibitors - Novel Perspectives for Psychiatric and Neurodegenerative Drug Discovery

Abstract: This review is based on peer-reviewed published articles, and summarizes the cellular and molecular biology of PDE10 as a rational target for psychiatric and neurodegenerative drug discovery. Here, we present the classification of PDE10-Is from a medicinal chemistry point of view across a wide range of different, drug-like chemotypes starting from theophylline and caffeine analogs, papaverine and dimethoxy catechol type PDE10-Is, TP-10, MP-10, MP-10/papaverine/quinazoline series inhibitors, and ending with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…In addition, PDE10A has also been detected in parenchymal parts of the substantia nigra, globus pallidus, and striatonigral projections [24]. Therefore, several studies have suggested PDE10A as a potential therapeutic target for movement disorders such as PD and HD, and psychiatric disorders that affect the basal ganglia [2527]. Currently, several PDE10A inhibitors are undergoing clinical trials in patients with HD and schizophrenia [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDE10A has also been detected in parenchymal parts of the substantia nigra, globus pallidus, and striatonigral projections [24]. Therefore, several studies have suggested PDE10A as a potential therapeutic target for movement disorders such as PD and HD, and psychiatric disorders that affect the basal ganglia [2527]. Currently, several PDE10A inhibitors are undergoing clinical trials in patients with HD and schizophrenia [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphodiesterases (PDEs) have been shown to play distinct roles in the processes of emotion, while selective PDE inhibitors can modulate mood and emotional states by preventing the breakdown of cAMP and/or cGMP. Some members of the PDE family, such as PDE4B and PDE10A, may be good drug targets because of their presence in areas of the brain associated with the site of action of psychotropic drugs, and their inhibitors therefore have potential therapeutic relevance [50]. Certainly, we could exclude the inhibition of PDE4B and PDE10A as a potential mechanism of antidepressant-like action of AZ-853 and AZ-861; this is because in a previous in vitro study using a bioluminescent detection system, we demonstrated that both compounds did not induce PDE4B and PDE10A inhibitory activity [8].…”
Section: Plos Onementioning
confidence: 99%
“…The phosphodiesterase 10A (PDE10A) enzyme is involved in cellular signaling pathways in schizophrenia. As a consequence, inhibitors of PDE10A offer a promising therapeutic approach for the treatment or prevention of psychiatric disorders, especially schizophrenia and related diseases [49].…”
Section: Biological Activity Of Cinnoline Derivativesmentioning
confidence: 99%